Bertumbuhnya Penduduk Bali Pasca-Reformasi (1998) - I Wayan Sudana (Badan Riset dan Inovasi Daerah Provinsi Bali, 2018)
Population is a capital in a development of a country but on the other side, it is also a problem for the development if the population is not well managed. A big amount of population will be potential to provide human resources. Such a big amount will be a great market for the domestic production but it will need the provision of foods, shirts, houses, jobs, and facilities of education, health, etc. This thing happens in Bali because this island is an international popular destination. In the post-reform (reformasi Indonesia), Bali population growth in 1998 has increased. This is caused by several factors, namely: TFR increase, positive net migration, and decreased mortality. There are many potential negative impacts that can arise because of the population problems due to the increase in the rate of growth. Therefore, in development, the population must be paid more attention, because in essence in the development of the population is as the subject and object. The development should be able to improve the welfare of the inhabitants either inborn or in a just and sustainable way